Pengaruh Media Puzzle Terhadap Hasil Belajar Siswa pada Materi Penjumlahan Bilangan Pecahan di Kelas 3 SD - Hery Setiyawan; Qonita Ayu Nabilah; Anisah Kurniasih (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of puzzle media on student learning outcomes in the material of adding fractions in grade 3 of elementary school. The method used is an experiment with a pretest-posttest control group design, where one group uses puzzle media in the learning process and the other group uses conventional methods. The population taken is the results of classes 3B and 3C. The sample of this study consists of two classes, namely the experimental class (using puzzle media) and the control class (not using puzzle media). The instrument used is an essay test of 5 pretest questions and 5 posttest questions. The results of the analysis using the t-test showed a significant difference between student learning outcomes in the experimental class and the control class. The use of puzzle media has been proven to improve students' understanding of the concept of fractions in a more enjoyable, active, and interactive way. Therefore, puzzle media can be used as an alternative effective learning media in improving student learning outcomes in mathematics, especially adding fractions.